The helminth derived peptide FhHDM-1 redirects macrophage metabolism towards glutaminolysis to regulate the pro-inflammatory response - Quinteros, Susel Loli; von Krusenstiern, Eliana; Snyder, Nathaniel W.; Tanaka, Akane; O’Brien, Bronwyn; Donnelly, Sheila (Frontiers in Immunology, 2023)
We have previously identified an immune modulating peptide, termed FhHDM-1, within the secretions of the liver fluke, Fasciola hepatica, which is sufficiently potent to prevent the progression of type 1 diabetes and multiple sclerosis in murine models of disease. Here, we have determined that the FhHDM-1 peptide regulates inflammation by reprogramming macrophage metabolism. Specifically, FhHDM-1 switched macrophage metabolism to a dependence on oxidative phosphorylation fuelled by fatty acids and supported by the induction of glutaminolysis. The catabolism of glutamine also resulted in an accumulation of alpha ketoglutarate (α-KG). These changes in metabolic activity were associated with a concomitant reduction in glycolytic flux, and the subsequent decrease in TNF and IL-6 production at the protein level. Interestingly, FhHDM-1 treated macrophages did not express the characteristic genes of an M2 phenotype, thereby indicating the specific regulation of inflammation, as opposed to the induction of an anti-inflammatory phenotype per se. Use of an inactive derivative of FhHDM-1, which did not modulate macrophage responses, revealed that the regulation of immune responses was dependent on the ability of FhHDM-1 to modulate lysosomal pH. These results identify a novel functional association between the lysosome and mitochondrial metabolism in macrophages, and further highlight the significant therapeutic potential of FhHDM-1 to prevent inflammation.